Comparison of the Effectiveness of Eye Movement Desensitization and Reprocessing and Mindfulness-Based Cognitive Therapy on Working Memory in Individuals with Primary Insomnia - Shariati , Behnoush; Sabet, Mehrdad; Ranjbaripour , Tahereh; Sodagar, Sheida; Mohammadi Shirmahaleh, Fatemeh (KMAN Counseling & Psychology Nexus, 2026)
Primary insomnia is one of the common disorders that has a significant negative impact on cognitive functioning, including working memory. The aim of the present study was to compare the effectiveness of Eye Movement Desensitization and Reprocessing (EMDR) and Mindfulness-Based Cognitive Therapy (MBCT) on working memory in individuals with primary insomnia. A total of 48 participants (16 in each group) were selected from among individuals with primary insomnia through convenience sampling while observing the inclusion criteria. They were then randomly assigned to two experimental groups and one control group. The research design was a quasi-experimental pretest–posttest design with a one-month follow-up. The data collection instrument was the N-Back Test (1958). Mixed ANOVA, Bonferroni post hoc test, and SPSS (Version 26) were used for data analysis. The results indicated that both Eye Movement Desensitization and Reprocessing and Mindfulness-Based Cognitive Therapy were effective in improving working memory in individuals with primary insomnia; however, there was no significant difference between the effectiveness of the two treatments. The findings of this study showed that both therapeutic approaches were effective in improving working memory. Nevertheless, future studies with larger sample sizes and long-term follow-ups are required to examine the stability of treatment effects and enhance the generalizability of the results.